2003
DOI: 10.1097/01.phm.0000078239.83545.d0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Noninvasive Positive-Pressure Ventilation in Patients with Amyotrophic Lateral Sclerosis

Abstract: Noninvasive positive-pressure ventilation provides a long-lasting benefit on symptoms and quality of life indicators for amyotrophic lateral sclerosis patients and should be offered to all patients with symptoms of sleep disordered breathing or inspiratory muscle dysfunction. It can also prolong tracheostomy-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 28 publications
2
32
0
3
Order By: Relevance
“…Although the data on NIPPV pressure settings required for comfort are quite limited, there is previous work describing pressures associated with arterial blood gas titration [18] that demonstrated improved pulmonary gas exchange with a very wide range of positive airway pressures, equivalent to 8.2 -22.4 cm H 2 0 pressure, supporting the notion that high levels of positive airway pressure are not necessary in all ALS patients. Unfortunately, titrating to arterial blood gases is not practical in ALS patients.…”
Section: Discussionmentioning
confidence: 93%
“…Although the data on NIPPV pressure settings required for comfort are quite limited, there is previous work describing pressures associated with arterial blood gas titration [18] that demonstrated improved pulmonary gas exchange with a very wide range of positive airway pressures, equivalent to 8.2 -22.4 cm H 2 0 pressure, supporting the notion that high levels of positive airway pressure are not necessary in all ALS patients. Unfortunately, titrating to arterial blood gases is not practical in ALS patients.…”
Section: Discussionmentioning
confidence: 93%
“…11 In the randomized controlled trial, Bourke et al used the symptom subscale of the Sleep Apnea Quality of Life Index (SAQLI) and found an improvement of symptoms in the total group and in patients with good bulbar function. 3 Patients with poor bulbar function had no improvement, except for the time-weighted mean of the SAQLI symptom score.…”
mentioning
confidence: 99%
“…Butz et al showed that patient-reported improvements in sleep emerge after one month of NIV treatment and could last for up to 10 months. 11 As the goal of NIV is improving sleep and QoL and simultaneously increasing survival, longitudinal studies on the effect of NIV on sleep and the effect of improved sleep quality on survival are definitely needed. We know that PSG is not routinely used during NIV titration in most countries.…”
mentioning
confidence: 99%
“…However, there is some evidence that patients who start mechanical ventilation using non-invasive ventilators are more likely to refuse invasive ventilation in the later stages (20,52). Non-invasive ventilation such as NIPPV can reverse respiratory failure and improve symptoms in neuromuscular and chest wall diseases (12,31,(53)(54)(55), ease sleep obstructive events (53,(56)(57)(58) and improve general quality of life (9,47,(59)(60)(61)(62)(63). Noninvasive ventilation is also a more cost-effective alternative to tracheostomy, as it does not require nurses to help with regular home care (8).…”
Section: Management Of Respiration In Als Patientsmentioning
confidence: 97%